Evaluating efficacy of organo-mineral fertiliser to meet nutrient demands of cereal crops in England - McKenna, Patrick; Burak, Emma; Harris, Jim A.; Sakrabani, Ruben (Elsevier, 2026)
Whilst mineral fertilisers are a reliable source of crop nutrients in conventional arable farming, their production is associated with significant environmental and economic challenges, including greenhouse gas emissions, price volatility, and nutrient leaching. Organo-mineral fertilisers (OMFs) have been proposed as a sustainable alternative, combining mineral nutrients with organic residues. This study investigated the potential of OMFs to supplement mineral fertiliser applications in arable farming across three field trials in England from 2022 to 2023. The trials examined the impact of an OMF derived from composted food waste added to potassium chloride and ammonium sulfate (8–3-3 + 19% SO3) on soil nutrient dynamics, grain yield, and crop quality in spring barley (Hordeum vulgare) and oats (Avena sativa). The results indicated that OMF application increased soil sulphur levels at two sites, suggesting its potential as a sulphur source for cereal crops. However, grain nutrient concentrations showed minimal response to OMF treatments compared to mineral fertilisers, with only minor differences observed in phosphorus, sulphur, and zinc levels. Yield responses varied by site, with OMF application resulting in slight reductions in barley grain and nitrogen yields compared to mineral fertiliser, particularly at higher nitrogen application rates. The oat trial showed no significant fertiliser effects, likely due to high inherent soil fertility and potential nutrient leaching. These findings highlight that while OMFs can contribute to nutrient cycling and sustainable fertiliser management, their effectiveness depends on formulation, nutrient release patterns, and site-specific factors such as soil fertility and weather conditions. The quality and composition of organic feedstocks within OMFs are critical to ensuring optimal synchronisation of nutrient availability with crop requirements, supporting their role in integrated nutrient management programs.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 2 Zero Hunger; Agronomy & Agriculture; 3002 Agriculture, land and farm management; 3004 Crop and pasture production